EVALUATION OF RURAL FUND MANAGEMENT IN COMMUNITY EMPOWERMENT PROGRAM - Inosensius Kefi; Nursalam Nursalam; Ajis Salim Adang Djaha (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to determine the evaluation of village fund management, empowerment of the Kaenbaun village community, supporting and inhibiting factors as well as those affecting the implementation of the use of village fund allocations in Kaenbaun village, East Miomaffo sub-district, North Central Timor district. This study uses a descriptive research method with a qualitative approach. The data analysis model used was the Miles and Huberman analysis model. The results showed that the management of village funds in Kaenbaun village, East Miomaffo sub-district was effective, efficient, sufficient, equitable, responsive and right on target. However, in terms of quality, there needs to be guidance for the management of village funds and community empowerment in Kaenbaun Village, Miomaffo Tmur District, North Central Timor Regency which is not fully locally based because in empowerment activities, they have not fully utilized the local potential in the village, and some resources are still imported from outside the village. However, the empowerment program implemented in Kaenbaun village had quite a positive impact on the community. The supporting factor for the implementation of village fund management and empowerment programs is obtaining village fund allocations and the inhibiting factor for village fund management and program implementation is the lack of unprofessional human resources so that the empowerment of village communities is not optimal. Keywords: Evaluation, management of village funds, community empowerment.